Subunits of human condensins are potential therapeutic targets for cancers - Wang, Hong-Zhen; Yang, Si-Han; Li, Gui-Ying; Cao, Xudong (Université d'Ottawa | University of Ottawa, 2018)
Abstract The main role of condensins is to regulate chromosome condensation and segregation during cell cycles. Recently, it has been suggested in the literatures that subunits of condensin I and condensin II are involved in some human cancers. This paper will first briefly discuss discoveries of human condensins, their components and structures, and their multiple cellular functions. This will be followed by reviews of most recent studies on subunits of human condensins and their dysregulations or mutations in human cancers. It can be concluded that many of these subunits have potentials to be novel targets for cancer therapies. However, hCAP-D2, a subunit of human condensin I, has not been directly documented to be associated with any human cancers to date. This review hypothesizes that hCAP-D2 can also be a potential therapeutic target for human cancers, and therefore that all subunits of human condensins are potential therapeutic targets for human cancers.